The Effectiveness of Sharia KUR Education in Improving Financial Literacy of MSMEs in Timur Indah Subdistrict, Bengkulu City - Angly Mayori; Khairiah Elwardah; Herlina Yustati (Jurnal Aghniya, 2025)
Background: MSMEs in Timur Indah Village, RT 09 RW 04, Bengkulu City, have not optimally utilized Sharia financing due to limited financial literacy. Pegadaian Syariah's KUR education program was conducted to improve the understanding of 30 MSMEs, encouraging them to transition from interest-based loans to halal financing. Method: Community-Based Research: location survey (April), participant identification (May), classroom-based education (July 19, 2025). Twenty-seven participants completed a pre-test and post-test with 15 questions; improvement in understanding was calculated descriptively as a percentage. Results: Attendance was 90% (27/30). The average pre-test score was 58, and the post-test score was 82. 92.6% (25/27) recorded an improvement, while 7.4% remained unchanged. Three participants immediately registered for Sharia KUR; active discussions demonstrated high interest Conclusion: The 2.5-hour education program significantly increased Sharia KUR literacy in the short term. Recommendations: expansion to other RTs, more interactive modules, and post-education mentoring to ensure funding realization.